Do direito linear ao direito complexo: contribuições da epistemologia da complexidade para a crítica ao positivismo jurídico nos manuais de ensino do direito - Fernandes, Marcel Sena (2010)
This work aims to find, by literature search and critical analysis, the reception of jus positivism in Brazilian law and to present by complexity theory a critique and an attempt to show a complex law. We tried to demonstrate that complexity theory provides insights into a critical analysis of legal positivism. The analysis has developed as a theoretical complexity of the epistemology of Edgar Morin. We analyzed manuals of study of the law from law courses in Brazil and works of Edgar Morin.